Keadilan Sosial dalam Kebijakan Makan Siang Gratis: Studi pada Sekolah di Wilayah Tertinggal di Kabupaten Merauke, Papua Selatan - Indra Kertati; Karningsih Karningsih; Christine DW (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2025)
This study aims to analyze the implementation of the Free Nutritious Meal Program (MBG) in underdeveloped regions, with a case study conducted in Merauke Regency, South Papua Province. The main focus is to examine to what extent the policy reflects the principles of social justice, particularly for vulnerable groups such as students from low-income families, indigenous communities, and those living in remote areas. This research adopts a descriptive qualitative approach using in-depth interviews, participatory observation, and document analysis. The findings reveal that the MBG program has positively contributed to student attendance, improved nutritional intake, and alleviated household economic burdens. However, disparities in access, logistical challenges, and resource limitations remain significant obstacles. From  social justice, the program has yet to fully meet the difference principle, as students in the most disadvantaged areas face the greatest barriers to access. Likewise, through the lens of capability approach, institutional limitations and a lack of community engagement hinder the program’s effective utilization. The study concludes that while MBG is a progressive public policy initiative, improvements are needed in implementation design, inter-agency coordination, and local-based approaches. Recommendations include strengthening logistics, promoting local food diversification, and establishing participatory evaluation mechanisms to ensure the program’s sustainability and equity.